Видатний архітектор Іван Могитич і сокілецька церква XII–XIII століть - Захар’єв, В. (Видавництво Львівської політехніки, 2014)
Йдеться про один з епізодів діяльності Народного архітектора України І. Могитича, а саме: перший етап робіт над реконструкцією давньоруської дерев’яної церкви ХІІ–ХІІІ ст., який виявив автор 1994 р. в урочищі Батарея поблизу с. Сокілець Дунаєвецького району Хмельницької області. The article refers to an episode of activity of the People’s architect I.Mohytycha Ukraine, namely: the first stage of works on the reconstruction of Old Russian wooden church in the twelfth and thirteenth centuries., Which was found by the author in 1994 in the tract near Battery s. Sokilets Dunayevets’kyi Khmelnitsky region region.
Keywords: ХІІ–ХІІІ ст.; Сокілець; Іван Могитич; дерев’яна церква; ур. Батарея; реконструкція; John Mohytych; reconstruction; the twelfth and thirteenth centuries; Ur. Battery; Sokilets; wooden church